Identifikasi variasi pola tata ruang tanean lanjhang di Kabupaten Sumenep, Jawa Timur - Mohammad Firman Tajul Arifin; Naniek Kohdrata; I Nyoman Gede Maha Putra (Jurnal Arsitektur Lansekap, 2025)
Tanean Lanjhang is a collection of houses owned by several families who are intertwined. At this time, many new houses have emerged that are no longer built based on the Tanean Lanjhang concept. This is due to the increase in population so that automatically the available land is getting narrower. The purpose of this study is to find out how the development of the Tanean Lanjhang spatial pattern and its variations today in Sumenep Regency. The method used in this research is a survey method by collecting data using observation techniques, interviews and literature study. The results of this study indicate that nowadays a lot of Tanean Lanjhang have undergone major changes in the shape of the house because the homeowners wanted a more comfortable home. There needs to be an effort to preserve this concept by including lessons on local architecture in the design curriculum, architects and landscape architects must also apply local wisdom in their designs, and the role of the government is also needed in establishing policies regarding the application of local wisdom in development in the regions.